2009
DOI: 10.1063/1.3187544
|View full text |Cite
|
Sign up to set email alerts
|

Proton transfer and H/D isotopic exchange of water molecules mediated by hydroxide ions on ice film surfaces

Abstract: The effect of hydroxide ions on proton transfer and H/D isotopic exchange of water molecules was examined at the surface of amorphous ice films at temperatures of 92-140 K. Excess hydroxide ions were provided onto a D(2)O-ice film by the hydrolysis of Na atoms, and H(2)O was adsorbed onto the surface for a submonolayer coverage. The H/D isotopic exchange between H(2)O and D(2)O molecules on the ice film surface was monitored as a function of reaction time and temperature by using the techniques of reactive ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Both conditions favor the breaking of the second coordination shell of the proton and reduce the likeliness of PT. The comparison of the energy barriers for waterhydronium exchange (of the order of 10 kJ/mol) indicates a general good agreement with available experimental data of activation energies for PT [69][70][71][72] as well as with results previously reported by other authors on equivalent PMFs barriers for proton transfer in water using a different approach, based on the so-called dissociative water potential [42].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Both conditions favor the breaking of the second coordination shell of the proton and reduce the likeliness of PT. The comparison of the energy barriers for waterhydronium exchange (of the order of 10 kJ/mol) indicates a general good agreement with available experimental data of activation energies for PT [69][70][71][72] as well as with results previously reported by other authors on equivalent PMFs barriers for proton transfer in water using a different approach, based on the so-called dissociative water potential [42].…”
Section: Discussionsupporting
confidence: 90%
“…Experimental data revealed values of the order of -10 kJ/mol for the activation energy of PT at the surface of polycrystalline ice films (at 135 K), when the PT is mediated by hydroxyl ions (reported by Moon et al [69,70] and Kim et al [71] from reactive ion scattering) and for PT in pure water (Luz and Meiboom [72], obtained by proton magnetic relaxation measurements). The values of the energy barriers reported in the present work (around 2.3 kcal/mol ∼ 10 kJ/mol for the unconstrained system at 300 K, see above) agree well with the order of magnitude of the experimental measurements and with those obtained by Lockwood and Garofalini [42] and from previous estimation of the PT activation energy [43] although they cannot be properly considered as equivalent to activation energies of PT.…”
Section: Potentials Of Mean Force For Proton Transfermentioning
confidence: 88%
“…Our DFT results suggest that protonation events may play a role in the compensation of XPR-induced metal-centered charges even at 20 K. Indeed, proton movements in proteins and model systems can occur at low temperatures at least within a single hydrogen bond, if not over longer distances within extended hydrogen-bonded networks (95)(96)(97). This may be taken as evidence that terminal and/or metal-bridging O(H) ligands in CtR2 are integrated in hydrogen-bonding interactions, for example, with water molecules.…”
Section: Structures Of Fefe and Mnfe Cofactors-ourmentioning
confidence: 80%
“…This is in qualitative good agreement (order of magnitude) with the 10 kJ/mol obtained by Moon et al [61,62] by means of a reactive ion scattering technique for the activation energy of PT at the surface of polycrystalline ice film, prepared at 135 K. Therefore, PT is an activated process at low temperatures and it requires to surmount an energy barrier of quite important magnitude. When the process of PT is mediated by hydroxide ions, the energy barrier has been measured at 9.6 kJ/mol [32]. It should be noted that at the different subintervals of temperatures (between 298 and 250 K, from 225 up to 175 K and from 175 to 100 K) different slopes can be obtained, revealing different behavior when the system is at liquid phase, which undergoes the phase transition from liquid to LDA ice and at the LDA ice phase (in all cases at temperature ranges different from experimental data, because of the present water model).…”
Section: B Dynamics Of Proton Transfermentioning
confidence: 99%
“…Ohmine and coworkers [29,30] have reported results from ab initio calculations and observed that PT in cubic ice Ic is still fast, but significantly less than in liquid water. Experiments on amorphous ice films by reactive ion scattering and low-energy sputtering have revealed that PT occurs up to temperatures of the order of 100 K [31,32]. A recent study by means of reactive ion scattering and infrared spectroscopy [33] indicates the existence of efficient proton-relay channels for hydronium on amorphous ice surfaces.…”
Section: Introductionmentioning
confidence: 99%